Development of a Numerical Model for the Approximation of Stress Distribution for a Single Vertical Backfilled Stope - Christopher Newman; Zach Agioutantis; Gabriel S. Esterhuizen (International Conference on Ground Control in Mining, 2018)
"As conventional underground deposits are continuing to be depleted, mining operations have been forced to produce at greater depths and in more geologically and geometrically challenging conditions. Over the past decade, there has been a global increase in the application of cemented paste backfill (CPB) material as a means of ground support in open stope mining operations. Although CPB has been extensively used within the industry, there are many fundamental factors affecting the design of safe and economical fill structures that are still not well understood. A critical design issue with respect to backfilled stopes is determining the stress state within the fill material as well as the surrounding rock.This paper details the development of a reliable numerical model for the simulation of stress distributions around the excavated stope area, as well as through the backfill material. Through discussions on modeling parameters and output results, one is provided with insights into the mechanisms of stress redistribution allowing for further accuracies in simulating the behavior of the CPB material as well as its interaction with the surrounding rockmass.INTRODUCTION AND BACKGROUNDModern technological innovations with respect to material processing, cementitious composition and chemical additives, and material transportation have provided the mining industry with a ground support material that greatly reduces mine waste costs, while, when used appropriately, increases reserve production and mine stability. As mining operations continue to produce in more complex geologic and geometric conditions, cemented paste backfill (CPB) has become commonly employed within primary-secondary excavation-support sequencing allowing for total extraction of the mining reserve. As shown in Figure 1, primary stopes are initially excavated and then backfilled in a two-staged pour: plug and final pours. The plug (initial pour), is initially placed at the bottom of the stope with a CPB material of heightened cementitious material. While the plug provides a strong foundation on which to build the rest of the CPB structure, it also provides protection against barricade breakthroughs (Li and Aubertin, 2009), as well as providing operations a means of underhand stope-and-fill mining through the use of an artificial sill pillar (Hughes, et al., 2011). Following placement, the plug is allowed to cure to a designated design strength. Upon completion of the plug, a less cementitious “final” pour material is used to backfill the rest of the excavated area."